Model Flyer Uji Publik Layanan Kebahasaan pada Materi Kesalahan Berbahasa Semeseter VII Prodi PBSI UMN Al-Washliyah - Abdullah Hasibuan; Tiflatul Husna; Nirmawan Nirmawan (Dinamika Pembelajaran : Jurnal Pendidikan dan bahasa, 2024)
This flayer media will be used in teaching language error analysis to find out the errors contained in the flayer as a promotion that is still relied on today. Language error analysis is used by language teachers to collect samples of errors, identify the errors contained in the samples, explain the errors, classify the errors, and evaluate the level of seriousness of the errors. The aim of this research is to find out how to analyze language errors and what language should actually be used in media flayers during promotions. This type of research is descriptive research with a qualitative approach. This research was carried out on seventh semester students of the PBSI UMN Al Washliyah Study Program. The population in this research was all 18 PBSI semester VII students. The sampling technique used in this research is a non-probability sampling technique. Media Flayer in language error analysis learning is considered effective for use in learning activities. Apart from being easy to access, media flayer also makes it easier for students to analyze language errors because just by using a mobile phone they can analyze language errors without having to go to the place they are going to. This research follow-up creates a comprehensive workflow from research results to real implementation and continuous improvement. This research has the potential to create positive and sustainable changes in various aspects of community life.